PELAKSANAAN WAKAF UANG PADA BANK SYARIAH DI INDONESIA - Sriani, Endang (Universitas Wahid Hasyim Semarang, 2025)
This study aims to analyze the enforcement of cash waqf at the bank of sharia Banking and to find out the constraint and the strategy conducted by sharia Banking as LKS-PWU. It is a field study by using empiric approach. The data collection techniques are observation, documentation and interview and the data are analyzed by descriptive method. The study results show that: (1) the enforcement of cash waqf at the sharia Banking can be conducted by online through the website or come to the sharia Banking immediately, whereas the waqf management (tasharruf) is more of the type of waqf by way of money (for physical development) than the cash waqf (financial investment). (2) The constraint relates to the duty and the function of Sharia Banking which are only limited to the receiving of cash waqf, Sharia Banking cannot optimize the management of cash waqf through the financial investment instrument, because the cash waqf goes to nazhir’s account directly then used by nazhir based on the wakif’s wishes. (3) The strategies which are undertaken by Sharia Banking to introduce and to increase the public interest to donate a money through LKS-PWU is by means of social media and various events held and attended by Sharia Banking.